Extraction of Sulfated Polysaccharide from Red Seaweed (𝙂𝙧𝙖𝙘𝙞𝙡𝙖𝙧𝙞𝙖 𝙛𝙞𝙨𝙝𝙚𝙧𝙞) and Growth Promotion of Probiotic Bacteria - Rormwong, Thanaporn; Sakpetch, Phat; Choojit, Saovanee; Kanjan, Pochanart (Burapha Science Journal, 2026)
The objective of this study was to optimize conditions to increase the yield of sulfated polysaccharides from red seaweed (Gracilaria fisheri) harvested between July (SP1) and October (SP2) 2020, extracted with distilled water. The effects of algae to water ratio (1:25, 1:35, and 1:50 (w/v), extraction time (40, 60, and 90 min), and extraction temperature (90, 100, and 110 °C) were investigated. The optimal conditions for sulfated polysaccharide extraction from red seaweed were algae materials to water 1:50 (w/v) at a temperature of 100 ºC for 60 minutes, with an obtained the yields of 13.80±4.24% (SP1) and 18.52±0.93% (SP2). The utilization of sulfated polysaccharide derived from red seaweed was performed for the growth of Lactobacillus paracasei TISTR 2389 and Lactobacillus acidophilus TISTR 875. L. acidophilus TISTR 875 significantly utilized the sulfated polysaccharide for growth when compared with glucose and GOS as carbon sources (p<0.05). These results indicated that the sulfated polysaccharides from red seaweed could act as a potential prebiotic compound for development of the functional foods.